Transcriptome Signatures of Atlantic Salmon—Resistant Phenotypes against Sea Lice Infestation Are Associated with Tissue Repair - Valentina Valenzuela-Muñoz; Cristian Gallardo-Escárate; Diego Valenzuela-Miranda; Gustavo Nuñez-Acuña; Bárbara P. Benavente; Alejandro Alert; Marta Arevalo (Genes, 2023)
Salmon aquaculture is constantly threatened by pathogens that impact fish health, welfare, and productivity, including the sea louse Caligus rogercresseyi. This marine ectoparasite is mainly controlled through delousing drug treatments that have lost efficacy. Therein, strategies such as salmon breeding selection represent a sustainable alternative to produce fish with resistance to sea lice. This study explored the whole-transcriptome changes in Atlantic salmon families with contrasting resistance phenotypes against lice infestation. In total, 121 Atlantic salmon families were challenged with 35 copepodites per fish and ranked after 14 infestation days. Skin and head kidney tissue from the top two lowest (R) and highest (S) infested families were sequenced by the Illumina platform. Genome-scale transcriptome analysis showed different expression profiles between the phenotypes. Significant differences in chromosome modulation between the R and S families were observed in skin tissue. Notably, the upregulation of genes associated with tissue repairs, such as collagen and myosin, was found in R families. Furthermore, skin tissue of resistant families showed the highest number of genes associated with molecular functions such as ion binding, transferase, and cytokine activity, compared with the susceptible. Interestingly, lncRNAs differentially modulated in the R/S families are located near genes associated with immune response, which are upregulated in the R family. Finally, SNPs variations were identified in both salmon families, where the resistant ones showed the highest number of SNPs variations. Remarkably, among the genes with SPNs, genes associated with the tissue repair process were identified. This study reported Atlantic salmon chromosome regions exclusively expressed in R or S Atlantic salmon families’ phenotypes. Furthermore, due to the presence of SNPs and high expression of tissue repair genes in the resistant families, it is possible to suggest mucosal immune activation associated with the Atlantic ...